Cultural scripts and the speech act of opinions in Irish English - Gąsior, Weronika (ELOPE (Ljubljana), 2015)
Studies in pragmatics have been limited to a handful of illocutionary acts such as requests, apologies or compliments, and opinions remain underrepresented in the existing literature. In this paper I present the results of a study of opinions in Irish English, conducted in an intercultural environment of Irish-Polish interactions. Departing from a traditional approach of speech act realisation studies, I applied the theory of cultural scripts to analyse opinions. In contrasting the Irish and Polish formulas for expressing opinions, as well as sociopragmatic attitudes towards this speech act, a difference in the cultural scripts for opinions in each culture was observable. Apart from already documented Polish frankness in opinions, the study discovered also a rational approach to presenting good arguments to support one's assertions among the participants. In relation to the Irish script for opinions, the findings are in line with previous classifications of opinions in Australian English, showing a certain level of variational uniformity amongst the English-speaking cultures in this regard.
Keywords: irska angleščina; izražanje mnenja; kulturni skripti; medkulturna pragmatika; poljščina